Metodología para el cálculo de coeficientes de sustentación y arrastre en perfiles aerodinámicos simétricos aplicado a turbinas Darrieus - Rolón Ortiz, Humberto Alejandro; Villamizar González, Yesenia; Acevedo Peñaloza, Carlos Humberto (Redes de Ingeniería, 2017)
Darrieus-type turbines have gained prominence as a source of clean energy. Due to the geometry of these turbines, their blades face wide ranges of angles of attack due to their circumferential displacement. In the following article, the coefficients of support and drag for each angle are characterized, starting from initial data generated in the software JavaFoil. The Montgomerie extrapolation method was implemented to derive the values at attack angles after the maximum lift coefficient and was compared with experimental data produced by Robert Sheldahl in the SANDIA laboratories, resulting in a close correlation between the data series.